Heavy metals contamination in shallow groundwater of a coal-mining district and a probabilistic assessment of its human health risk. Issue 3 (3rd April 2019) - Qiu, Huili; Gui, Herong
Abstract: To manage public health and make better use of groundwater resources, the concentration characteristics and a health risk assessment of eight heavy metals in shallow groundwater were studied. Besides this, this paper introduced triangular fuzzy numbers into the USEPA health risk assessment model to assess the health risk posed to local children and adults through different exposure pathways. The results showed that Mn levels exceeded the WHO's guideline values of 100 µg/L with the proportion of 27.98% and Sr were over the health reference level (HRL) of 1500 µg/L with the proportion of 56.25%, while other heavy metals were below the corresponding standard. The results of the HRA showed that the non-carcinogenic risks from Sr and Mn in the district were relatively higher, while those from the remaining six heavy metals were relatively lower. All hazard index (HI) values did not exceed the safety level of 1 for either age group. The average carcinogenic risk from Cr was slightly higher than the acceptable level of 1 × 10 −6 for adults. Sensitivity analyses conducted using Monte Carlo simulation indicated that Sr and Cr concentrations were the most influential variables contributing to the non-carcinogenic and carcinogenic risk values, respectively, while body weight had a minor contribution.